Ghosts & Live Wires : Balthus - Brancusi - Brassai - Calder - Duchamp - Walker Evans - Giacometti - Anne Harvey - Leger - Raymond Mason - Masson - Matisse - Miro - Pascin - Picasso - Man Ray - Carl Van Vechten - Burns, Edward; Dudley, Dorothy; Geist, Sidney; Harvey, Steven (New York : Gallery Schlesinger, 1990)
Balthus ; Brancusi, Constantin ; Brassaï ; Calder, Alexander ; Duchamp, Marcel ; Evans, Walker ; Giacometti, Alberto ; Harvey, Anne ; Leger, Fernand ; Man Ray ; Mason, Raymond ; Masson, Andre ; Matisse, Henri ; Miro, Joan ; Pascin, Jules ; Picasso, Pablo ; Steichen, Edward ; Van Vechten, Carl
Engels
Ghosts & Live Wires, Gallery Schlesinger, New York, February 1990
boek